Design of a water quality monitoring system powered by a Savonius hydrokinetic turbine - Tinoco Villa, Josue Marshall (2025)
Water quality monitoring is essential due to the constant variation in its properties caused by pollutants, environ- mental changes, or other factors. This paper proposes the design of a real-time water quality monitoring system powered by a Savonius turbine. The VDI 2221 guideline is used for the design process. The proposed system measures temperature, electrical conductivity (EC), pH, dissolved oxygen (DO), total dissolved solids (TDS), turbidity, and pressure. The total energy consump- tion of all components is 32.92Wh. The Savonius turbine was analyzed using two-dimensional computational fluid dynamics (CFD). It was found that at a water velocity of 1.02m/s, the turbine, under load conditions, torque coefficient of 0.28, and power coefficient of 0.322, the alternator reached 150RPM. Under these conditions, the alternator provides 100Wh, satisfying the energy consumption of the system.